Ageing across the Tasman Sea: the demographics and health of older adults in Australia and New Zealand - Paul Kowal; Andy Towers; Julie Byles (Elsevier, 2014)
Abstract Objective: The demographic and health aspects of ageing populations in Australia and New Zealand (NZ) are described. These data are relevant to compare impacts of policy and context in each country. Methods: Secondary analysis of international (Organization for Economic Co‐operation and Development, United Nations and World Health Organization) and domestic population and health data. Results: Both countries will experience a greater than 80% increase in the population aged 60‐plus years between 2013 and 2050. The increase in the 80‐plus population will be 200% or higher, resulting in 2.8 million Australians and more than 510,000 New Zealanders in this age group by 2050. The speed of ageing in both countries is higher than the average rate of increase in developed countries. Average life expectancy at birth and age 60 is higher in Australia than NZ, with the differences increasing slightly by 2050, and gaps between men and women consistently smaller in NZ than in Australia. However, a higher proportion of older Australians report living with a disability (53%) than older New Zealanders (45%). Conclusions: Australia and NZ are well aged in the context of a youthful Oceania region, with more similarities than differences between the countries. Implications: Both countries need to continue to monitor health trends, unravel the major population attributable risks, and identify preventative and other interventions that can stimulate and support declines in disability in older populations in the future, particularly for non‐indigenous older persons.